Emissions of atmospherically reactive gases nitrous acid and nitric oxide from Arctic permafrost peatlands. (1st February 2022) - Bhattarai, Hem Raj; Marushchak, Maija E; Ronkainen, Jussi; Lamprecht, Richard E; Siljanen, Henri M P; Martikainen, Pertti J; Biasi, Christina; Maljanen, Marja
Abstract: Soils are important sources of nitric oxide (NO) and nitrous acid (HONO) in the atmosphere. These nitrogen (N)-containing gases play a crucial role in atmospheric chemistry and climate at different scales because of reactions modulated by NO and hydroxyl radicals (OH), which are formed via HONO photolysis. Northern permafrost soils have so far remained unexplored for HONO and NO emissions despite their high N stocks, capacity to emit nitrous oxide (N2 O), and enhancing mineral N turnover due to warming and permafrost thawing. Here, we report the first HONO and NO emissions from high-latitude soils based on measurements of permafrost-affected subarctic peatlands. We show large HONO (0.1–2.4 µ g N m −2 h −1 ) and NO (0.4–59.3 µ g N m −2 h −1 ) emissions from unvegetated peat surfaces, rich with mineral N, compared to low emissions (⩽0.2 µ g N m −2 h −1 for both gases) from adjacent vegetated surfaces (experiments with intact peat cores). We observed HONO production under highly variable soil moisture conditions from dry to wet. However, based on complementary slurry experiments, HONO production was strongly favored by high soil moisture and anoxic conditions. We suggest urgent examination of other Arctic landscapes for HONO and NO emissions to better constrain the role of these reactive N gases in Arctic atmospheric chemistry.